Peningkatan Hasil Belajar Aqidah Akhlaq Melalui Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Siswa Mts.S Al-Alim Maligano - Ety Nur Inah; Martiani Martiani (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
This study aims to improve student learning outcomes Aqidah Akhlaq through the implementation of cooperative learning model Think Pair Share (TPS) class VIII MTs.S Al-Alim Maligano. This type of research is the Classroom Action Research (PTK) is the implementation of the action research / treatment directly by using learning model, in this study using a pair of cooperative learning model Think Share (TPS). This learning model consists of three phases the first phase Think (think), the second phase Pair (pairs) and Phase Sharing (sharing). Thinking phase, the research object is a class VIII student MTs.S Al-Alim Maligano. Techniques of data collection is done by observation sheets, test and documentation and data analysis techniques. The results obtained after conducting research that is: the first cycle of daily student test scores ranged from 75-90 with an average value of 73.29 grade students completed as many as 26, An increase in value of 19.3% of students in accordance KKM is 75. In cycle II daily student test scores ranged from 75-99 with an average value of 84.76 class with an average increase of 11.7 class so as to increase the percentage of 88.23% compared to the first cycle second cycle increased total of 30 out of 34 students have already reached 75 KKM limit of 80% of the planned target.Keywords: Cooperative type Think Pair Share (TPS), learning outcomes